SHORT-TERM OUTCOMES OF VERY LOW BIRTH WEIGHT INFANTS IN RIGA MATERNITY HOSPITAL - Kovale, Sabine; Vasioleka, Beate; Sperberga, Anete; Zaharane, Elizabete Marta; Laizane, Evija; Galica, Polina; Rasnaca, Kristine; Sleiers, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
As the preterm birth rate is increasing in most countries, the number of very low birth weight infants (VLBW - birth weight less than 1500 grams) is also growing. VLBW infants are at a high risk of morbidity and mortality, but the adverse outcomes have been decreasing over the last few years due to improvements in the quality of care. The main objective of this research is to determine the risk factors of early neonatal morbidity, rate of survival, frequency of disease and complications in VLBW infants as well as to compare the differences between the years. The data was collected from the Riga Maternity hospital’s medical records over a five-year period from 2015 to 2019. A total of 209 VLBW were admitted to the Riga Maternity hospital’s intensive care unit, of whom 192 (92.3%) survived to discharge. Over the five years the number of VLBW infants increased almost by half, while the mortality rate fluctuated between the years. Respiratory distress syndrome and sepsis were the two main complications for the infants. More than half (62.5%) of non-survivors died within the first 24 hours after birth with respiratory failure being the leading cause. Survival rate was strongly associated with gestational age and birth weight.